Vliv profylaktické mastektomie s rekonstrukcí na kvalitu života žen s BRCA pozitivitou - Spurná, Z; Dražan, L; Foretová, L; Dvorská, L (Klinicka onkologie, 2012)
UNLABELLED: It is presumed that bilateral mastectomy is so far the most efficient way how to prevent development of breast carcinoma among BRCA positive patients. This mutilating intervention might be unacceptable for cosmetic reasons for most women. The purpose of this study was to determine the influence of prophylactic mastectomy on the quality of life of BRCA positive patients by comparing results of psychodiagnostic questionnaire methods before surgical intervention and after it. Our data set consisted of 25 BRCA positive healthy women and 19 BRCA positive women in remission. All these patients underwent a reconstructive surgical intervention after mastectomy. Age of patients was 38-55 years. The following questionnaires were used: Life Satisfaction Questionnaire by J. Fahrenberg, M. Myrtek and E. Brähler, Clinical analysis questionnaire by S. E. Kruge and R. B. Cattel, Impact of Event Scale - Revised by D. S. Weiss and C. R. Marmar. RESULTS: Women in remission showed most significant decrease in Financial position category and minor decrease in Work and Employment category and Friends, Acquaintances and Relatives category. Improvement of quality of life was recorded especially in category of Health, Sexuality, Own person, Partnership and in Relationship with own children and there was also a significant improvement to overall life satisfaction. Among healthy patients, there was a significant improvement in category of Health and Own person. Most significant decrease was in dimension of Financial position and Work and employment. Prophylactic mastectomy with reconstruction might be the way of prevention of breast carcinoma because from psychological point of view there is the unambiguously significant fact that there was improvement of perception of own health and own person in both groups of women. These are the quality of life aspects that are considered to be basal and long term stabilizing from the perspective of dynamics of own self and they also systematically influence other aspects of quality of life which are derived from them.
Keywords: Mammaplasty; geny BRCA2; Breast Neoplasms; Mastectomy; geny BRCA1; Middle Aged; průzkumy a dotazníky; mutace; Adult; kvalita života; Genes, BRCA1; Genes, BRCA2; ženské pohlaví; Mutation; Humans; Surveys and Questionnaires; lidé středního věku; nádory prsu; dospělí; mamoplastika; Female; Quality of Life; mastektomie; lidé